1995
DOI: 10.1016/s0006-3495(95)80220-1
|View full text |Cite
|
Sign up to set email alerts
|

Stages of the bilayer-micelle transition in the system phosphatidylcholine-C12E8 as studied by deuterium- and phosphorous-NMR, light scattering, and calorimetry

Abstract: The perturbation of phospholipid bilayer membranes by a nonionic detergent, octaethyleneglycol mono-n-dodecylether (C12E8), was investigated by 2H- and 31P-NMR, static and dynamic light scattering, and differential scanning calorimetry. Preequilibrated mixtures of the saturated phospholipids 1,2-dipalmitoyl-sn-glycero-3-phosphorylcholine (DPPC), 1,2-dimyristoyl-sn-glycero-3-phosphorylcholine (DMPC), and 1,2-dilauroyl-sn-glycero-3-phosphorylcholine (DLPC) with the detergent were studied over a broad temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
76
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 58 publications
8
76
1
Order By: Relevance
“…This line of reasoning is supported by recent molecular dynamics simulations providing transversal distribution of the entropy and free energy of hexane (which mimics an acyl chain segment) in phospholipid bilayers (60). It is also supported by the fact that acyl chain length has much less influence with octyl glucoside micelles, since these are far more disordered than lipid bilayers (61), and the orientational order of acyl chains of incorporated phospholipids (when minor components, as in this study) also changes little with depth as indicated by data obtained with similar systems (62).…”
Section: Discussionsupporting
confidence: 67%
“…This line of reasoning is supported by recent molecular dynamics simulations providing transversal distribution of the entropy and free energy of hexane (which mimics an acyl chain segment) in phospholipid bilayers (60). It is also supported by the fact that acyl chain length has much less influence with octyl glucoside micelles, since these are far more disordered than lipid bilayers (61), and the orientational order of acyl chains of incorporated phospholipids (when minor components, as in this study) also changes little with depth as indicated by data obtained with similar systems (62).…”
Section: Discussionsupporting
confidence: 67%
“…[18][19][20][21][22][23][24][25][26] These results provide a physicochemical basis for the purification and functional reconstitution of complex transmembrane proteins into unilamellar vesicles. There are hundreds of studies on this subject, but a few noteworthy examples pertinent to this study include the proteotypical G-protein coupled receptor, bacteriorhodopsin (bR), 27 and a ligandgated ion channel responsible for fast signal transduction, the serotonin receptor (5HT3R).…”
Section: Introductionmentioning
confidence: 82%
“…The partitioning of the surfactant molecules between the lipidic assemblies and the aqueous continuum can be modified by three categories of procedures: surfactant extraction, dilution and temperature variation. With respect to the last approach, it has been shown that temperature-induced transition from micelles to bilayer structures occurs in phospholipid containing systems involving octylglucoside (Miguel 1989), C 12 E 8 (Otten 1995) and bile salts (Polozova, 1993;Polozova, 1995;Forte, 1998) for appropriate lipid / detergent ratios. The temperature variation procedure allows to perform MVT without changing the total lipid and surfactant concentrations in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are applied to study the aggregation behaviour of mixed lipid-detergent systems and MVT processes: time-resolved fluorescence (Das, 1996;Seras 1994), cryotransmission electron microscopy (Meyuhas, 1997;Silvanter, 1996;Seras, 1996), static and dynamic light scattering (Miguel, 1989;Polozova, 1995;Forte, 1998;Egelhaaf 1994), gel exclusion chromatography (Lesieur, 1990), differential scanning calorimetry (Otten, 1995;Forte 1998), NMR (Otten, 1995;Polozova, 1993). Compared to light or neutron scattering (Long, 1994;Pedersen, 1995;Hjelm, 1992;Kiselev, 1999) small-angle X-ray scattering (SAXS) is generally not considered as a convenient technique for phospholipid vesicle characterisation (Van Zanten, 1996).…”
Section: Introductionmentioning
confidence: 99%